2004
DOI: 10.1152/jn.00107.2004
|View full text |Cite
|
Sign up to set email alerts
|

Second-Order Vestibular Neurons Form Separate Populations With Different Membrane and Discharge Properties

Abstract: Straka, H., M. Beraneck, M. Rohregger, L. E. Moore, P.-P, Vidal, and N. Vibert. Second-order vestibular neurons form separate populations with different membrane and discharge properties. J Neurophysiol 92: 845-861, 2004. First published March 24, 2004 10.1152/ jn.00107.2004. Membrane and discharge properties were determined in second-order vestibular neurons (2°VN) in the isolated brain of grass frogs. 2°VN were identified by monosynaptic excitatory postsynaptic potentials after separate electrical stimulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 47 publications
1
24
0
Order By: Relevance
“…This synaptic uncoupling can be achieved by modifying the artificial cerebro-spinal fluid (ACSF), e.g., with high Mg 2+ /low Ca 2+ ACSF (Vibert et al, 2000; Darlington et al, 2002), or with a cocktail of synaptic blockers (Ris et al, 2001a; Guilding and Dutia, 2005) as well as by complete isolation from other structures (Darlington and Smith, 2000). The 2° VN intrinsic properties, and in particular those of neurons from the medial vestibular nucleus, have been described in many Vertebrates, including Rats (Gallagher et al, 1985; Johnston et al, 1994), Mice (Dutia et al, 1995; Johnston and Dutia, 1996), Guinea pigs (Serafin et al, 1991a,b), Amphibians (Straka et al, 2004), and Chicks (du Lac and Lisberger, 1995; Gottesman-Davis and Peusner, 2010; Gottesman-Davis et al, 2011). In all Vertebrates, medial 2° VN form a heterogeneous population dominated by tonic and phasic neurons (Straka et al, 2005; Eugène et al, 2007; Grassi et al, 2009; Camp et al, 2010).…”
Section: Description Of 2° Vn Basic Intrinsic Propertiesmentioning
confidence: 98%
See 1 more Smart Citation
“…This synaptic uncoupling can be achieved by modifying the artificial cerebro-spinal fluid (ACSF), e.g., with high Mg 2+ /low Ca 2+ ACSF (Vibert et al, 2000; Darlington et al, 2002), or with a cocktail of synaptic blockers (Ris et al, 2001a; Guilding and Dutia, 2005) as well as by complete isolation from other structures (Darlington and Smith, 2000). The 2° VN intrinsic properties, and in particular those of neurons from the medial vestibular nucleus, have been described in many Vertebrates, including Rats (Gallagher et al, 1985; Johnston et al, 1994), Mice (Dutia et al, 1995; Johnston and Dutia, 1996), Guinea pigs (Serafin et al, 1991a,b), Amphibians (Straka et al, 2004), and Chicks (du Lac and Lisberger, 1995; Gottesman-Davis and Peusner, 2010; Gottesman-Davis et al, 2011). In all Vertebrates, medial 2° VN form a heterogeneous population dominated by tonic and phasic neurons (Straka et al, 2005; Eugène et al, 2007; Grassi et al, 2009; Camp et al, 2010).…”
Section: Description Of 2° Vn Basic Intrinsic Propertiesmentioning
confidence: 98%
“…The functioning of the vestibular system critically depends on the range of head movements produced during locomotion (Straka et al, 2004; Beraneck and Straka, 2011). The synaptic and intrinsic properties of 2° VN are co-adapted and match these behavioral requirements.…”
Section: Perspectives For Future Researchmentioning
confidence: 99%
“…With respect to various morpho-physiological properties such as resting discharge rate and regularity, afferent fibers of both larval (Gensberger et al, 2016) and adult frogs (Honrubia et al, 1989) form a broad spectrum. Despite the apparent continuum of distinguishing features, afferent fibers in Xenopus tadpoles segregate into two distinct categorical groups (Gensberger et al, 2015) with physiological characteristics, reminiscent of phasic and tonic 2°VN of adult frogs (Straka et al, 2004). The obvious duality of the vestibular afferent population in Xenopus larvae complies with a separation into frequency-tuned pathways as a major organizational principle of the VOR (Straka et al, 2009) and its implementation already early after hatching.…”
Section: Functional Organization Of Vestibular Circuitriesmentioning
confidence: 99%
“…In contrast, changes in intrinsic membrane properties of vestibular neurons after a loss of one labyrinth as shown in guinea pig (Beraneck et al, 2003, 2004) have so far not been reported in frog. However, this is not due to a general absence of such a plasticity phenomenon in frog, but rather due to the lack of respective studies that compare known intrinsic neuronal properties of frog tonic and phasic 2°VN (Straka et al, 2004; Beraneck et al, 2007) before and after the lesion. Assuming the presence of basic reaction mechanisms that only differ in magnitude between different species, a general hypothesis is derived from the results obtained in guinea pigs after UL (Beraneck et al, 2003, 2004).…”
Section: Peripheral and Central Vestibular Plasticity After Unilateramentioning
confidence: 99%